Long-term survival rates of titanium implants placed in expanded alveolar ridges using split crest procedures: a systematic review (2020)
Purpose: To evaluate the survival rates of titanium dental implants placed using split crest procedures for alveolar ridge expansion. Materials and methods: The MEDLINE, CENTRAL, and OpenGrey databases were searched up to January 2015 for studies assessing implants that had been placed in areas submitted to split crest procedures. Two methodologic quality-assessment tools were used based on the type of study. For randomized controlled trials (RCTs), the Cochrane Collaboration tool was used to assess the risk of bias. For the observational studies, an adapted version of the Newcastle-Ottawa scale was used. Results: A total of 1,178 patients received 3,033 implants with ridge expansion. On average, the success rate was 96.6% and the survival rate was 96.8%, with a mean follow-up of 58.3 months. Six of the nine included studies used a bone substitute associated or not with a membrane, and seven studies used an implant in both the maxilla and mandible. In addition, half of the observational studies were considered to be of medium quality, whereas the others were considered to be of low quality; the sole RCT included was classified as having a high risk of bias. Conclusion: The use of split crest techniques appears to provide predictable alveolar ridge augmentation as well as high survival rates in the short and long term for implants placed in the maxilla or mandible. Patients must be selected with caution.